(untitled) (Pakistan Journal of Science, 2022)
Today, most urban areas of less developed countries are at the verge of multifarious environmental problems and vehicular transportation sector is considered to be significant contributor to this degradation in the urban environment. The current study is based on a detailed soil survey conducted for heavy metal’s analysis in the road side soil of Faisalabad city. The heavy metal induced into the road side soil has been recognized as a serious threat to human health through ingestion and inhaling. Soil samples from sixteen points were taken at a depth of 5 to 15cm in the vicinity of some selected congested road sides. The heavy metal contents were analyzed through the ICP (inductively coupled plasma spectroscopy) for the Zn, Cu, Pb, Ni, As and Cd. Out of these six, two metals (As and Cd) were not traced by ICP. The study was conducted aiming at investigating the heavy metal contents in road side soil and to generate the spatial map for an in-depth analysis. The conclusion designed after descriptive statistics and distribution patterns of roadside soil delineated through the spatial interpolation of inverse distance weight using ArcGIS 10, which revealed that there were a number of hotspots for Zn, Cu, Ni and Pb with mean concentration ranged from 19.2-336.8, 11.25-73.20, 13.38-29.70 and0.00-27.05 mg/kg while a decreasing order of heavy metals mean values on all the selected roads are Zn>Cu>Ni>Pb.